FIKIH SOSIAL KIAI SAHAL SEBAGAI FIKIH PERADABAN - Asmani, Jamal Ma'mur (Faculty of Shariah and Law, State Islamic University (UIN) Walisongo, 2014)
Thought of â€˜Fikih Sosialâ€™ Kiai Sahal Mahfudh is a method to explore and respond to the dynamics of law in society. â€˜Fikih Sosialâ€™ is a model of fiqh development based maá¹£laá¸¥ah oriented with a clear manhaj. As an embryo of â€˜fikih peradabanâ€™ (civilizing fiqh), â€˜Fikih Sosialâ€™ was based on the method of the underlying ideas of Moslem scholars (â€˜ulamÄâ€™), not a product of their thoughts. Therefore, to follow the method, may result the same product and the different one as well. The method is to contextualize â€˜traditional authoritative bookâ€™ (al-kutub al-muâ€™tabarah) through the undestanding of the applications of rules of uá¹£Å«l al-fiqh or qawÄâ€™id al-fiqhiyyah. The development of masÄlik al-'illah theory is also urgent in accordance with producing fikih based maá¹£laá¸¥ah al-'Ämmah. In this position, fikih Kiai Sahal completely answers the problem of the integration of authenticity and modernity which are often contradictory and antagonistic